Development and validation of an assessment for measuring chemical literacy in chemical equilibrium - Pratama, Faiz Ilham; Hariyanti, Sherly; Rohaeti, Eli (Jurnal Pendidikan Kimia, 2024)
Chemical literacy, the ability to integrate the understanding of chemistry with everyday life phenomena, has become a necessary skill for high school students. This skill is aimed at enabling students to develop an understanding of chemistry concepts about the environment, health, and industrial topics. This research focuses on developing and validating a chemical literacy assessment, specifically on chemical equilibrium. Afterward, the assessment was given the name Chemical Equilibrium Literacy Assessment. The development model is based on modified 4D and consists of two sets of 15 questions each. Content validity was measured using the Aiken V equation with seven expert judgments and four answer categories. To assess construct validity, the Pearson equation was used involving 100 respondents. The reliability of the assessment was calculated using Cronbach's Alpha. The results of content validity, construct validity, and quality of test items indicate that the chemical literacy assessment on chemical equilibrium material on environmental, health, and industrial topics has relatively high results. This assessment can be used to measure the chemical literacy abilities of high school students after studying chemical equilibrium.